The legal review of parking liability for vehicle loss according to the consumer protection law - Fadliyah, Ulfa; Asnawi, Asnawi; Faturohman, Faturohman (Institute Of computer Science (IOCS), 2025)
The loss of motor vehicles in paid parking areas frequently occurs without clear accountability from parking operators. Many operators include liability exemption clauses on parking tickets, such as